T-Scan guided occlusal equilibration as an effective treatment in the management of symptomatic temporomandibular disorders: An open clinical trial - Ancy V Ignatius; Komali Garlapati; Nallan CSK Chaitanya; Asra Saba; Pallavi Kandi; Chelluri Shreya Reddy (Wolters Kluwer Medknow Publications, 2022)
Background: Temporomandibular disorders (TMDs) constitute clinical problems that involve the masticatory muscles, the temporomandibular joints, associated structures, or both. The etiology of TMDs is multifactorial. The association between occlusal interferences and TMD is controversial.. Objectives: This study is designed to evaluate the clinical outcome of T-Scan guided occlusal equilibration in patients suffering from TMD associated with occlusal discrepancies. Materials and Methods: A total of 15 patients clinically diagnosed with TMD based on the Diagnostic Criteria for Temporomandibular Disorders and with positive occlusal interferences were included in the study. The occlusal equilibration was achieved by performing T-Scan guided Immediate Complete Anterior Guidance Development. Results: The obtained data was subjected to statistical analysis using SPSS version 20.0 software. There was a statistically significant reduction in the occlusion time, i.e., from 0.77 ± 0.6 pre-treatment to 0.31 ± 0.2 post-treatment (P = 0.005), and also disclusion time, i.e., from 1.71 ± 1.09 pre-treatment to 0.11 ± 0.03 post-treatment (P = 0.000). There was a statistically significant reduction in the VAS score post-treatment (P = 0.000). Conclusion: T-Scan guided occlusal equilibration in TMD patients has resulted in significant improvement of symptoms. Hence, we emphasize the importance of the identification and correction of occlusal interferences in the management of symptomatic TMDs.